Proses Analogi Siswa Sekolah Dasar dalam Mengajukan Masalah Luas Daerah - Firdatus Nurlaila; Mohammad Faizal Amir (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
This study analyzes the analogy process when elementary school students in pose area problems. This research used a qualitative method with a case study approach. The participants in this study were fifth-grade students of SD Negeri 1 Krembung, totaling 53 students. The selection of participants was made purposively. Data were collected using tests, interviews, and observations. Data analysis techniques used data reduction, data presentation, and conclusion drawing. Indicators of analogy process assessment based on Gentner Forbus's theory are retrieval, mapping, abstraction, representation, and evaluation. The results of this study indicate that elementary school students can use analogies in the learning process, but in the analogy process, there are differences between some students. The problems proposed by students are categorized as varied problems and complete processes, varied and incomplete processes, not varied and incomplete processes. In this study, it is suggested that novice elementary school students posing problems should use analogies as a reasoning process so that in posing new problems, they can come up with creative ideas.